Pierisin, Cytotoxic and Apoptosis-Inducing DNA ADP-Ribosylating Protein in Cabbage Butterfly - Takahashi-Nakaguchi, Azusa; Horiuchi, Yu; Yamamoto, Masafumi; Totsuka, Yukari; Wakabayashi, Keiji (Toxins, 2024)
Pierisin-1 was serendipitously discovered as a strong cytotoxic and apoptosis-inducing protein from pupae of the cabbage butterfly Pieris rapae against cancer cell lines. This 98-kDa protein consists of the N-terminal region (27 kDa) and C-terminal region (71 kDa), and analysis of their biological function revealed that pierisin-1 binds to cell surface glycosphingolipids on the C-terminal side, is taken up into the cell, and is cleaved to N- and C-terminal portions, where the N-terminal portion mono-ADP-ribosylates the guanine base of DNA in the presence of NAD to induce cellular genetic mutation and apoptosis. Unlike other ADP-ribosyltransferases, pieisin-1 was first found to exhibit DNA mono-ADP-ribosylating activity and show anti-cancer activity in vitro and in vivo against various cancer cell lines. Pierisin-1 was most abundantly produced during the transition from the final larval stage to the pupal stage of the cabbage butterfly, and this production was regulated by ecdysteroid hormones. This suggests that pierisn-1 might play a pivotal role in the process of metamorphosis. Moreover, pierisin-1 could contribute as a defense factor against parasitization and microbial infections in the cabbage butterfly. Pierisin-like proteins in butterflies were shown to be present not only among the subtribe Pierina but also among the subtribes Aporiina and Appiadina, and pierisin-2, -3, and -4 were identified in these butterflies. Furthermore, DNA ADP-ribosylating activities were found in six different edible clams. Understanding of the biological nature of pierisin-1 with DNA mono-ADP-ribosylating activity could open up exciting avenues for research and potential therapeutic applications, making it a subject of great interest in the field of molecular biology and biotechnology.